IDENTIFIKASI JENIS MANGROVE PADA NEGERI HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Worabai, Salomina Selfiana; Sahupala, Andjela; Komul, Yulianus (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Mangrove forests are one of the unique and distinctive forest ecosystem forms found in coastal areas or small islands as highly potential natural resources. Mangroves have high economic and ecological value but are vulnerable to damage if not utilized wisely. Mangrove ecosystems have important functions and benefits in coastal environments consisting of three main functions: physical, biological, and economic. Physical functions include erosion prevention, seawater intrusion barriers, wind barriers, and CO₂ reduction. Plant identification can be defined as an activity to reveal and establish the identity of plants, which in this case is determining the correct plant names and their proper place in the classification system. This research aims to identify mangrove species found in Hatusua State, Kairatu District, West Seram Regency. Based on the identification results of mangrove plant species at the research location, 15 plant species were found, divided into two groups. The true mangrove group consists of 5 species: Rhizophora apiculata, Sonneratia alba, Bruguiera gymnorrhiza, Bruguiera sexangula, and Avicennia lanata. The associate mangrove group consists of 7 species: Excoecaria agallocha, Xylocarpus moluccensis, Heritiera littoralis, Cerbera manghas, Dolichandrone spathacea, Aegiceras corniculatum, and Xylocarpus granatum. Additionally, understory plants were also found, such as Acrostichum speciosum, Acanthus ilicifolius, and Derris trifoliata. The results of this study indicate relatively high mangrove species diversity at the research location and can serve as a foundation for conservation efforts and sustainable mangrove ecosystem management.